Respuesta :

Answer:

(-6,2)

Step-by-step explanation:

[tex]x = - 6 \\ x - y = - 8[/tex]

Substitution

Substitute x = -6 from the first equation in the second equation.

[tex] - 6 - y = - 8 \\ - 6 + 8 = y \\ 2 = y[/tex]

Normally, we have to substitute either x-term or y-term in one of the equation to get another term. For this situation, we already know the value of x so It is not necessary to substitute the y-value.

Answer Check

We have to check the answer to make sure that we have got the right answer.

We can check the answer by substituting both x-value and y-value in the equation.

[tex]x - y = - 8[/tex]

Substitute x = -6 and y = 2 in the equation.

[tex] - 6 - 2 = - 8 \\ - 8 = - 8[/tex]

The equation is true. Therefore, our answer is (-6,2)